2017
DOI: 10.3390/polym9070254
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Response of Human Peripheral Blood Mononuclear Cells (PBMC) to Collagen Films Treated with Cold Plasma

Abstract: The implantation of biomedical devices, including collagen-based implants, evokes an inflammatory response. Despite inflammation playing an important role in the early stages of wound healing, excessive and non-resolving inflammation may lead to the poor performance of biomaterial implants in some patients. Therefore, steps should be taken to control the level and duration of an inflammatory response. In this study, oxygen and nitrogen gas plasmas were employed to modify the surface of collagen film, with a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…While IL-8 and IL-1β are related to immune rejection, IL-10 inhibits the production of different pro-inflammatory cytokines, including IL-8 and IL-1β, and is associated with immune acceptance . In this regard, the results obtained for donor 2 point to a controlled immune response, where the secretion of pro- and anti-inflammatory cytokines is balanced . However, it must be stressed out that none of the values were above the ones measured when in presence of lipopolysaccharide, the positive control.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While IL-8 and IL-1β are related to immune rejection, IL-10 inhibits the production of different pro-inflammatory cytokines, including IL-8 and IL-1β, and is associated with immune acceptance . In this regard, the results obtained for donor 2 point to a controlled immune response, where the secretion of pro- and anti-inflammatory cytokines is balanced . However, it must be stressed out that none of the values were above the ones measured when in presence of lipopolysaccharide, the positive control.…”
Section: Discussionmentioning
confidence: 86%
“…60 In this regard, the results obtained for donor 2 point to a controlled immune response, where the secretion of pro-and anti-inflammatory cytokines is balanced. 63 However, it must be stressed out that none of the values were above the ones measured when in presence of lipopolysaccharide, the positive control. This result suggests that GG-MA/PLL PEC beads do not exerted per se a serious inflammatory reaction that could compromise the functionality of this system as an immunoprotective matrix for cells.…”
Section: ■ Discussionmentioning
confidence: 87%
“…In our former study [ 58 ], we suggested not to analyse the specimen directly after treatment because this approach can overestimate antimicrobial performance, which can be circumvented either by longer incubation [ 58 ] or by the cultivation of osteoblasts on treated discs [ 70 ]. This approach works with discs but not with implants because it is difficult to protect cleaned from contaminated areas in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…hPBMCs have been widely used as an in vitro model to investigate biocompatibility and inflammation; thus, they were used in this work [22]. The hPBMCs were extracted using a density gradient [23].…”
Section: Isolation Of Human Peripheral Blood Mononuclear Cells (Hpbmcs)mentioning
confidence: 99%